Comparative Study on Structural Steel Bondek II Decking for Composite Floor Connections: Design Analysis in Compliance with EN 1994-1-1: 2004 - Faisal Amsyar, Redzuan; Abdul Razak, Abdul Karim; Norsuzailina, Mohamed Sutan; Norazzlina, M.Sa'don; Siti Farhanah, SM Johan (Springer Nature, 2025)
Due to their enhanced load-bearing capacity and structural effectiveness, composite slabs – which integrate concrete and profiled steel sheeting – are essential to recent industrial building. The structural performance, endurance and sustainability of these systems are greatly enhanced by the combination of concrete, which provides compressive strength, and Lysaght Bondek II profiled steel sheeting, which provides tensile reinforcement. In accordance with EN 1994-1-1: 2004, this study reevaluates the design of composite floor systems employing Bondek II profiled steel sheeting. The design of composite steel and concrete structures is outlined in Eurocode 4: Part 1-1: General rules and building regulations. The goal is to compare the results of manual Excel calculations with those obtained from MegaFloor software for both construction/formwork and composite (slab) stages. A case study was conducted using Bondek II, a hot-dipped, zinc-coated high-tensile steel, considering various span lengths and load conditions. The partial connection approach, in accordance with EN 1994-1-1: 2004, was used to evaluate shear resistance and bending moments. The analysis revealed a high level of agreement between the manual calculations and the software outputs, with only minor differences in bending moment and shear force values. However, significant discrepancies were captured in the shear (web crippling) capacity, suggesting the need for further validation through an experimental program. Ultimately, the study affirms that MegaFloor software is a reliable tool for composite floor system design, adhering to both British Standards and Eurocodes. The integration of modern software tools with traditional design methods enhances the accuracy, efficiency and sustainability of construction practices.